PROCESS OPTIMIZATION OF SAUSAGE PRODUCED FROM RABBIT MEAT USING RESPONSE SURFACE METHODOLOGY - Omobolanle Omowunmi OLORODE; Olamiji Funke ADEDEJI (Food and Environment Safety, 2023)
This study investigated the process optimization of sausage produced from rabbits. Response surface methodology was used to investigate the effect of cooking time (45-60 minutes), frying temperature (170-190 °C) and frying time (45-60 minutes) resulting into seventeen experimental runs. The rabbit meat was pre-cooked and frying was carried out using an electric deep fryer with a temperature control of ±10 °C. Proximate composition (moisture content, total ash, crude fat, crude fibre, crude protein and total carbohydrate content) colour (lightness, redness and yellowness) and textural properties (hardness, springiness, adhesiveness, cohesiveness and chewiness) was carried out on the sausage from rabbit meat using standard laboratory procedures. The moisture content, total ash, crude fat, crude fibre, crude protein and total carbohydrate content ranged from 56.98-59.64%, 0.93-5.92%, 13.41-17.18%, 0.32-2.41%, 12.53-15.60% and 5.37-9.41%. Also, the range of values for lightness, redness and yellowness were: 31.08-45.33, 2.58-6.83 and 10.31-20.32 respectively. However, cooking time, frying temperature and frying time had no significant (p>0.05) effect on hardness, springiness, adhesiveness, cohesiveness and chewiness respectively. The study shows that proximate composition and colour properties of sausage produced from rabbit meat were significantly affected by the independent variables (cooking time, frying temperature and frying time). However, the optimum condition of leading to desirable proximate composition, colour and textural properties is 45minutes of cooking time, 180 °C of frying temperature and 9 minutes of frying time.